Types and causes of damage to the conveyor belt – Review, classification and mutual relations. (October 2022) - Bortnowski, Piotr; Kawalec, Witold; Król, Robert; Ozdoba, Maksymilian
Highlights: A comprehensive review of the types of damage to the conveyor belt is presented. The set of causes of each type of failure is described in detail. Ad hoc and advanced repair methods have been suggested. The correct choice of condition monitoring for each operating condition has been substantiated. The basics of a damage management system based on archiving and processing information about previous faults are presented. Abstract: The belt is the most important working element of any conveyor. Damages to this element cause costly downtimes in the operation of the transport system. Due to the working conditions and contact with the material, it is exposed to damage. Proper operation can be the way to effectively extend the life cycle of a belt. The experience of users shows that the majority of belt damages are due to improper operation of the conveyor or the technical condition of components. The article presents an overview of the types of belt damages and the authors' classification of their causes, not directly related to the quality of production of the belt itself. For each type of damage, the right method of prevention and condition monitoring is presented. Decision diagrams were constructed to form the basis for proper management of the work and durability of the belt.